Human milk bank and its importance for mothers and babies: the great value of breastfeeding (Research, Society and Development, 2022)
The human milk bank are centers specialized in the promotion, collection and processing of breast milk, as well as offering services to raise awareness of the importance and value of breastfeeding. Objective: Compare and discuss the articles with those found on the topic: Milk bank and its importance in the promotion, protection and encouragement of breastfeeding. Methodology: A systematic search was carried out in the Pubmed/Medline, Scielo and Lilacs databases. Selecting publications from the last 5 years, including articles in languages ​​(English, Spanish and Portuguese), using the descriptors: Milk bank, Breastfeeding and Prematurity. Thus, the data obtained were organized into categories: the impact of breastfeeding and nutritional value; factors associated with breastfeeding; and the importance of the Human Milk Bank (BLH). Results: 22 publications were identified on the importance of milk banks and the impacts of breastfeeding for mothers and babies, of which 17 articles were selected for review. 5 articles were excluded, studies that were not available for free or were difficult to understand after translation. The HMB were highlighted as guarantors of breastfeeding and human milk with important benefits in preventing and fighting infections, especially for high-risk newborns. Conclusions: There are several productions that highlight the importance of HMB support, the value of breastfeeding and the importance of breastfeeding in preventing infections and recovering premature newborns.